Mixture deposition method for graphene quantum dots-based dye-sensitized solar cell - Mahalingam S.; Manap A.; Lau K.S.; Omar A.; Chelvanathan P.; Chia C.H.; Amin N.; Mathews I.J.; Afandi N.F.; Rahim N.A. (Elsevier Ltd, 2023)
Efficiency; Graphene; Graphene quantum dots; Light absorption; Mixtures; Nanocrystals; Photosensitizers; Semiconductor quantum dots; Titanium dioxide; Affinity; Charge collection efficiency; Deposition methods; Dye- sensitized solar cells; Electron collections; High charges; Higher efficiency; Layer by layer; Layer-by-layer assemblies; Photo-anodes; Dye-sensitized solar cells